Green waste compost: growing media for flowering annuals and environmental sustainability - SHARMA, SUKHDEEP KUMAR; DUBEY, R K; SINGH, SIMRAT; BALA, MADHU; SHARMA, SANDEEP; PANT, KRITIKA; PATEL, UMA (Journal of Ornamental Horticulture, 2025)
The escalation of green waste production within urban localities has introduced a pressing concern in disposal practices. One sustainable solution to address this issue is the practice of green waste composting. To better comprehend the required level of amendments, a research study was undertaken to investigate the impact of various green waste compost-amended growing media on the growth of four flowering annuals: Dianthus chinensis, Calendula officinalis, Bellis perennis and Tagetes patula. The study was conducted during 2020-2021 at Landscape Nursery, Department of Floriculture and landscaping, Punjab Agricultural University, Ludhiana. The seedlings were transplanted in polybag (two sizes viz., 7" × 5" and 12" × 10"), filled with Green Waste Compost (GWC) and soil in different proportions i.e., GWC only; GWC + Soil (3:1); GWC + Soil (1:1); GWC + Soil (1:3); FYM + Soil (1:1) (Check) and Soil (Control). GWC + Soil (1:1) in larger polybags had maximum number of flowering buds per plant (38.81), plant height (41.81 cm), plant spread (34.23 cm) and maximum number of branches per plant (24.20). Hence, the finding suggested that green waste compost + soil (1:1) was ideal for the production of annuals in nurseries.